The impact of educational expenditures of government on economic growth of Iran (2017)
Using the annual data of Iran’s economy from 1981-2012,  this study examines Wagner’s law and the Keynesian hypothesis about the relationship between the real government expenditure and the real GDP. In this regard, this paper investigated the relationship between  the total government expenditure, the GDP and the relationship between government educational expenditure and GDP using  bivariate  and multivariate models. The multivariate model is used to reduce the specified error issues that has not been considered in many studies.  The co-integration was examined using the auto regressive distributive lag method (ARDL) of both long-term and short-term  relationships.  In making the estimations  of the Wagner’s view, the variables: real GDP, capital stock and labor force stock respectively, had a positive, a negative, and a positive impact on total government expenditure and the long-term relationship is true in this regard.  Additionally, in the estimation  of Keynesian model, the educational expenditures, unlike real expenditures of government, had a long-term relationship. In addition, the variable, capital, in both models had a similar effect on the real GDP, and  the labor force coefficient in the presence  of the total expenditures and educational expenditures were negative and positive respectively.